2011
DOI: 10.2478/s11536-011-0086-1
|View full text |Cite
|
Sign up to set email alerts
|

Pseudocyesis as a cause of abdomen enlargement in a female adolescent

Abstract: AbstractPseudocyesis is a rare condition in the pediatric population characterized by all signs and symptoms of pregnancy except the existence of a fetus [1]. In some patients it is associated with organic etiology, in others with mental disorders, also occurs in those without disorders in their medical history. Pseudocyesis occurs in both sexes, but more frequently in women. An effective treatment is a combination of psychotherapy and pharmacotherapy with antidepressants and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…A deficiency of dopamine is often observed in pseudocyesis; dopamine inhibits the gonadotropin-releasing hormone, luteinizing hormone (LH) and prolactin levels ( 13 , 32 , 36 ). Studies revealed that catecholamine and dopamine deficiency are responsible for hyperprolactinemia ( 8 , 10 , 37 ). Elevated prolactin levels lead to galactorrhea or lactation, the persistence of corpus luteum, and suppression of Follicle-stimulating hormone and LH secretion, ultimately resulting in amenorrhea ( 13 , 14 , 25 , 29 , 35 , 36 , 38 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A deficiency of dopamine is often observed in pseudocyesis; dopamine inhibits the gonadotropin-releasing hormone, luteinizing hormone (LH) and prolactin levels ( 13 , 32 , 36 ). Studies revealed that catecholamine and dopamine deficiency are responsible for hyperprolactinemia ( 8 , 10 , 37 ). Elevated prolactin levels lead to galactorrhea or lactation, the persistence of corpus luteum, and suppression of Follicle-stimulating hormone and LH secretion, ultimately resulting in amenorrhea ( 13 , 14 , 25 , 29 , 35 , 36 , 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…In different contexts, some synonyms for pseudocyesis (a few of which are no longer in common use) have included pseudopregnancy, imaginary pregnancy, simulated pregnancy, phantom pregnancy, hysterical pregnancy, and spurious pregnancy ( 8 - 10 ). With pseudocyesis, physiological manifestations of pregnancy occur, including irregular menstruation (e.g., amenorrhea or hypo-menorrhea), abdominal distention, the subjective sensing of fetal movements, changes in breast size or shape, milk secretion, darkening of areolar tissue, galactorrhea, weight gain, nausea and vomiting, and changes in the uterus and cervix ( 6 , 7 , 11 - 13 ).…”
Section: Introductionmentioning
confidence: 99%
“… 18 Pseudocyesis commonly occurs in females who are in the reproductive age group of 20–44, 17 mainly in those in their late 30s. However, there are some reports that the problem has been observed in female teenagers 18 , 19 , 20 , 21 , 22 , 23 and, surprisingly, in preteen 24 and 6‐year‐old girls. 14 , 25 …”
Section: Discussionmentioning
confidence: 99%
“…18 Pseudocyesis commonly occurs in females who are in the reproductive age group of 20-44, 17 mainly in those in their late 30s. However, there are some reports that the problem has been observed in female teenagers [18][19][20][21][22][23] and, surprisingly, in preteen 24 and 6-year-old girls. 14,25 The case has also been observed in males, [26][27][28][29] although most of the cases in males would not be categorized under pseudocyesis based on the latest standards.…”
Section: Outcome and Follow-upmentioning
confidence: 99%
“…It has been reported that pseudocyesis commonly occur in females who are in the reproductive age group between 20 and 44 (16), mainly the late 30s. However, there are some reports that the problem was observed in female teenagers (15,(17)(18)(19)(20)(21) and, surprisingly in a pre-teen (22) and six years old girls (14,23). The case was also observed in a in males (24)(25)(26)(27), though most of the cases in male would not be categorized under pseudocyesis based on the latest standards (5).…”
Section: Lessons Learnedmentioning
confidence: 99%